Hubungan Pengetahuan, Sikap, dan Tindakan Penjamah Makanan Dengan Hygiene Sanitasi Makanan Pada Pedagang Kaki Lima di Kecamatan Rappocini, Kota Makassar - Muh.Ikbal Arif; La Taha La Taha; Ni Luh Astri Indraswari; Putri Putri (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2026)
Food handlers are people who work directly or come into contact with food, from selecting ingredients to serving food. Direct contact with food can be a source of contamination if hygiene and sanitation rules are not followed. Street vendors in Banta-bantaeng Village operate in a high-traffic area with limited facilities. An initial survey showed that many food handlers did not properly apply food hygiene and sanitation, such as not washing hands, not using personal protective equipment (masks, gloves, head coverings), and washing utensils using water that was used repeatedly. This poses a high risk of food contamination and outbreaks of food poisoning. This study aimed to determine the relationship between food handler behavior (knowledge, attitude, practice) and food hygiene sanitation among street vendors in Banta-bantaeng Village, Rappocini District, Makassar City. The type of research was an analytical observational study with a cross-sectional approach. Samples were taken using simple random sampling, consisting of 72 respondents from a population of 88 food handlers who used carts. Data were collected through questionnaires and direct observation. Data analysis used the Chi-Square test with SPSS. The results showed a significant relationship between food hygiene sanitation and knowledge (p=0.003), attitude (p=0.007), and practice (p=0.000). A total of 37 respondents (51.4%) met the requirements for food hygiene sanitation, while 35 respondents (48.6%) did not meet the requirements. The conclusion of this study is that knowledge, attitude, and practice of food handlers are significantly related to food hygiene sanitation. It is recommended that vendors pay more attention to personal hygiene and use PPE when processing food. Future researchers are advised to conduct Total Plate Count (TPC) examinations on the eating utensils used by street vendors